Developing a Responsive Islamic Education Curriculum to the Issues of Religious Moderation and Tolerance - Pujianti, Etika; Syafi'I, Ahmad; Al-Ansori, M. Zein; Javan, Muhammad Kamal Akbar; Nasution, M. Rifai; Sulaiman, Dedek; Hasibuan, Abdul Rahman (International Journal on Advanced Science, Education, and Religion, 2025)
The development of the Islamic Religious Education (PAI) curriculum in Indonesia faces significant challenges in addressing issues of religious moderation and tolerance within a diverse society. PAI is required not only to emphasize normative aspects but also to foster inclusive, tolerant attitudes and social skills among students to live harmoniously in the global era. The aim of this study is to analyze strategies for developing a PAI curriculum that is responsive to religious moderation, focusing on the integration of moderate Islamic values ​​with multicultural education needs, and to propose an applicable and contextual curriculum model. This study employed a qualitative approach with library research methods, collecting data from relevant literature such as books, journal articles, and educational policies. The findings reveal that a PAI curriculum responsive to religious moderation can serve as a transformative instrument in shaping a generation of Muslims who are inclusive, tolerant, and contributive to social harmony. In conclusion, the PAI curriculum should be designed in a multidisciplinary manner and supported by educational policies and teacher capacity building to ensure effective and sustainable implementation.